Combination of Electromyography and Electroencephalography Measurements in Designing Repetitive Task in Industry - Zadry, Hilma Raimona; Md Dawal, Siti Zawiah; Taha, Zahari (American Scientific Publishers, 2011)
A study was conducted to investigate the effect of low and high pace levels on upper limb muscles and brain activities in repetitive light task. Surface electromyography (EMG) was used to measure upper limb muscle activities of twenty subjects. The results show that the Mean Power Frequency (MPF) of the brachioradialis activities decreased as time increased, that reflects muscle fatigue. Electroencephalography (EEG) was simultaneously recorded with EMG to record brain activities from Fz, Pz, O1 and O2 channels. Mean power of the EEG alpha bands from the Fz-Pz channels were found to be higher on the HR task compared to LR task on EEG channels. The results indicated that HR task require more brain activities than the LR task. It is also found that there was significant and high relation between upper limb muscles and brain activities while performing repetitive light task. It signified that the longer the time and the more repetitive of the task, the subjects will be more fatigue physically and mentally. Thus the combining method has indicated promising empirical findings in designing repetitive light task with more concrete quantitative evidence. © 2011 American Scientific Publishers.